2009
DOI: 10.4049/jimmunol.0800455
|View full text |Cite
|
Sign up to set email alerts
|

Functional Killer Ig-Like Receptors on Human Memory CD4+ T Cells Specific for Cytomegalovirus

Abstract: Although very few CD4+ T cells express killer Ig receptors (KIR), a large proportion of CD4+ T cells with a late memory phenotype, characterized by the absence of CD28, does express KIR. Here, we show that KIR expression on CD4+ T cells is also associated with memory T cell function, by showing that the frequency of CMV-specific cells is higher in CD4+KIR+ than CD4+KIR− T cells. In addition, engagement of an inhibitory KIR inhibited the CMV-specific proliferation of these CD4+KIR+ memory T cells, but had no de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…Interestingly, HCMV‐specific CD8 T cells almost completely lack KIR expression, and the specificity of KIR‐expressing cells remains largely unknown 2, 5, 7, 151, 179. In contrast, it was shown that KIR +  CD4 + T cells display specificity against HCMV but not Epstein–Barr virus or HSV‐1 4. It is clear that inhibitory and activating KIR can, respectively, dampen and co‐stimulate T‐cell receptor‐mediated activation in CD4 and CD8 T cells 5, 151, 179, 180, 181, 182.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…Interestingly, HCMV‐specific CD8 T cells almost completely lack KIR expression, and the specificity of KIR‐expressing cells remains largely unknown 2, 5, 7, 151, 179. In contrast, it was shown that KIR +  CD4 + T cells display specificity against HCMV but not Epstein–Barr virus or HSV‐1 4. It is clear that inhibitory and activating KIR can, respectively, dampen and co‐stimulate T‐cell receptor‐mediated activation in CD4 and CD8 T cells 5, 151, 179, 180, 181, 182.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…42 Furthermore, celiac disease has been associated with the appearance of KIR ϩ intraepithelial CD8 T cells in the gut lumen, 43 and rheumatoid arthritis caused an accumulation of KIR ϩ CD28 Ϫ CD4 T cells. 21,23 Because most available antibodies against KIRs display cross-reactivity and recognize both activating and inhibitory receptor forms, the role of activating KIRs in the context of these autoimmune conditions could not be examined in detail on primary cells in those published studies. With the use of an established flow cytometric panel that includes KIR2DS4 and allows discrimination of KIR2DS1 from KIR2DL1, our analysis found that CD8 T cells frequently express activating KIRs.…”
Section: Kir2ds4mentioning
confidence: 99%
“…18 Other than NK cells, CD4 and CD8 T cells as well as ␥␦ T cells also express KIRs. [19][20][21][22][23][24] With respect to CD8 T cells, KIR expression starts to appear on effector memory CD8 cells, and a substantial fraction of terminally differentiated effector CD8 T cells are KIR ϩ . 20,22,25 The function of KIRs on CD8 T cells has been studied to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…KIR + T cells were first identified two decades ago (10), and were found in the CD8 + , CD4 + , TCR γδ+, and αβ + T-cell fractions (8, 11–15). Most KIR + T cells are αβ + CD8 + , possess a memory phenotype, and are generated upon TCR recognition of HLA-E–associated viral peptides after monoclonal or oligoclonal expansion (1618).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous TCR engagement sustains their KIR expression with resultant resistance to apoptosis (19–23). These cells are important in the control of infections such as cytomegalovirus (CMV) and hepatitis C virus infections (14, 15, 18, 24, 25). KIR expression and function are fundamentally different in T cells and NK cells (26).…”
Section: Introductionmentioning
confidence: 99%